Composition and composite material

By suspending silver particles in a mixture of deoxidizer solvent and co-solvent, and sintering at low temperature, a composite material with high electrical and thermal conductivity is formed. This solves the problem of sintering traditional silver sintering materials under high temperature and high pressure, and achieves good adhesion to different material surfaces and efficient manufacturing.

CN119301702APending Publication Date: 2025-01-10NATIONAL UNIVERSITY OF SINGAPORE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042114.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-17
Filing Date
2023-05-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing silver sintered materials are sintered at high temperatures and pressures, making it difficult to achieve high electrical and thermal conductivity at low temperatures. Furthermore, they exhibit poor adhesion to different material surfaces, and traditional polymer adhesives limit their applications.

Method used

Silver particles are suspended in a mixture of deoxidizing solvent and co-solvent, and a composite material is formed by low-temperature sintering below 200°C. The deoxidizing solvent and co-solvent provide the chemical reagents required for the reduction of silver oxide, avoiding high pressure and reducing atmosphere. Modifying polymers are used to improve the adhesion of silver particles.

Benefits of technology

It enables the formation of composite materials with high electrical and thermal conductivity at low temperatures, improves adhesion to different material surfaces, simplifies the manufacturing process, and reduces costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301702A_ABST
    Figure CN119301702A_ABST
Patent Text Reader

Abstract

The present disclosure provides a composition comprising a deoxidizer solvent, a co-solvent, and a plurality of silver particles suspended in a mixture of the deoxidizer solvent and the co-solvent wherein the deoxidizer solvent comprises one or more compounds of formula CnOmH2n + 2-p (OH) p wherein n, m and p are integers with the proviso that 1 < = (n + m) / p < = 8, and wherein the mixture of the deoxidizer solvent and the co-solvent comprises hydroxyl groups at a concentration of from 2M to 20M. A method of forming the composition is also provided. A method of forming the composite material and an apparatus comprising the composite material are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of Related Applications

[0002] This application claims priority to Singapore Application No. 10202205139Y filed with the Intellectual Property Office of Singapore on May 17, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention generally relates to a composition comprising a deoxidizer solvent, a cosolvent, and a plurality of silver particles suspended in a mixture of the deoxidizer solvent and the cosolvent. The present invention also relates to a method of forming the composition. The present invention also relates to a method of forming a composite material from the composition and a device comprising the composite material. Background Art

[0004] In order to meet the challenges of next-generation devices, especially high-power and high-speed electronic devices related to 5G, high-performance conductive and thermally conductive materials are needed as thermal interfaces, die attachment, electrical interconnects, and electrode materials. Thermal interface materials provide thermal contact between semiconductor chips and their heat sinks, while die attachment materials bond the chips to their substrates or packaging materials, and usually also provide electrical and / or thermal contact. Electrical interconnects and electrode materials provide contacts, bus bars, antennas, and wiring, such as in solar cells, switches, capacitors, sensors, and other printed electronic devices.

[0005] Traditionally, powder-based silver (Ag) sintered materials have attracted considerable attention due to their potential high electrical conductivity (6.2×10 5 S / cm) and thermal conductivity (430W / mK) and high melting temperature (961°C), these properties together provide high performance and high temperature tolerance. They have demonstrated excellent manufacturing and operational reliability. Silver sintering materials can be formulated into pastes suitable for high-volume, low-cost deposition methods, including syringe dispensing, screen printing and gravure printing, flexographic printing or other printing technologies. In addition, they are 'green' and environmentally friendly, containing no hazardous materials such as mercury, cadmium and lead. Copper is a possible alternative to silver, but copper also faces many challenges, especially the harsh conditions required for sintering and the resulting tendency to oxidize.

[0006] Although silver sintering paste has advantages and has been widely used, there are still some common challenges. Silver powder, which is mainly used in flake form, usually needs to be sintered for a long time at a sintering temperature far above 250°C and a high pressure (greater than 5MPa) to achieve a sintering temperature greater than 1.0×10 5S / cm and 75 W / mK. Although this sintering method is traditionally referred to as "low temperature sintering", the required temperature and time are not ideal for future thermal management and electrical interconnect technologies.

[0007] Furthermore, sintering requires the formation of local silver bridges between adjacent silver particles in the powder at temperatures well below its melting point. This process is not fully understood, but it is known to depend on the decomposition or reduction of native Ag2O on the surface of the silver particles to silver. The Ellingham diagram shows that Ag2O is thermodynamically unstable, especially since silver decomposes at temperatures above 147°C, but its activation energy is high. The deoxidation reaction of Ag2O can only proceed at an appreciable rate in air or nitrogen at temperatures above 300°C. However, in a reducing atmosphere of carbon monoxide, hydrogen or ethylene, the reaction can occur at much lower temperatures, below 200°C. However, such a reducing atmosphere also presents its own challenges, which may not be desirable in the manufacture of electrical materials.

[0008] Furthermore, without special pretreatment, pure sintered silver films generally adhere well to silver, gold, platinum and palladium layers and substrates metallized with these layers, but do not adhere to other materials such as semiconductors, oxides and plastics. This presents a special problem for thermal interface materials, since the total thermal resistance is the sum of the bulk resistance through the thermal interface material and the contact resistance at the two interfaces. To minimize thermal resistance, the interface material needs not only to have high thermal conductivity, but also good thermal conductivity at both interfaces. This generally requires good adhesion to both the die and the surface of the substrate or heat sink.

[0009] To improve adhesion, another conventional sintering material includes a thermosetting resin such as an acrylate, epoxy, polyimide, polyurethane or polysiloxane in the formulation to provide a polymer matrix. The resin can be prepolymerized or polymerizable in a reactive one-pot or two-pot formulation. This conventional material is known in the art as an electrically conductive adhesive (ECA), but its electrical and thermal conductivity is still limited.

[0010] Specifically, the above conventional materials generally provide good adhesion to many surfaces (better than 3 MPa lap shear strength), but at the expense of low bulk electrical and thermal conductivity, less than 7×10 4 S / cm and 50W / mK, even after sintering at 200°C or higher.

[0011] In addition, there are several main types of silver sintering pastes that are traditionally known, each with its own advantages and limitations. For example, micron silver pastes are based on micron-sized silver flakes with a diameter of 0.2 μm to 20 μm, produced by ball milling, and are therefore coated with grinding aids such as oleic acid or stearic acid. In order to obtain good performance, they usually require a sintering temperature of 200°C or higher (usually 250 to 300°C) and a sintering pressure of 0.5 MPa or higher (usually 2 to 5 MPa). These traditional materials have the longest development history and have proven to be reliable.

[0012] There are many paste improvements that are traditionally known to reduce sintering temperatures and improve adhesion. For example, Ag(I) compounds (e.g., oxides, formates, and carbonates) with low decomposition temperatures and oxidants can be added to reduce the required sintering temperature when these compounds decompose into silver at temperatures below their normal sintering temperatures and bridge between filler powders. Oxidants, such as organic and inorganic peroxides, can also be added to promote oxidative degradation and volatilization of organic coatings on silver powders. This also helps to reduce the sintering temperature, but this poses a risk to the reliability of the substrate and the die. Acidic fluxes and reducing agents can also be added to remove oxide layers on metallized surfaces (e.g., copper) to promote their adhesion to the sintered silver. Nevertheless, when sintered in an inert atmosphere at a temperature of 200°C or less and a pressure of 2MPa or less, the electrical conductivity and thermal conductivity of the paste are typically still less than 1.0×10 5 S / cm and less than 75 W / mK. Pressure sintering at a temperature of about 230 to 250°C and a pressure of more than 3 MPa is usually required to achieve higher conductivity.

[0013] Nanosilver pastes are also conventionally known and are generally based on nanoscale silver crystals suspended in a polymer binder. The silver filler is produced by chemical reduction of silver(I) salts in the presence of a capping ligand or agent such as methyloctylamine, dodecylamine, hexadecylamine, myristyl alcohol, 1-dodecanol, 1-decanol, stearic acid, oleic acid, palmitic acid or dodecanethiol. The capping ligand or agent is required to stabilize the silver nanocrystals. The required high volume fraction of the capping agent (usually exceeding 65 volume percent of the total solids) generally delays sintering until above 250°C. Polymer binders include poly(diallyldimethylammonium chloride), polyvinylpyrrolidone, polyacrylic acid, polystyrene sulfonate, polyvinyl alcohol, polyvinyl butyral and ethylcellulose. For nanosilver particles with short ligands with sparse and submonolayer coverage, 1.0×10 5The sintering temperature required for a conductivity of 1.5 S / cm can be reduced to 150°C. This suggests that shell volatilization, rather than surface melting as previously thought, determines the sintering temperature of nanocrystals, and thus the sintering temperature can be controlled by ligand selection. Nevertheless, nanosilver paste requires chemical synthesis of nanosilver, which is much more expensive and laborious than producing silver powder by grinding. In addition, the environmental and health effects of nanomaterials are still under discussion.

[0014] Traditionally, mixed silver pastes are also known. These pastes combine micron-sized and nano-sized silver particles to obtain higher packing density. Typically, the diameter ratio of a bimodal preparation is about 3:x (where x≤1), and the corresponding weight ratio is about 2:1. The diameter ratio of a trimodal preparation is about 10:3:x, and the weight ratio of the majority to the combined smaller portion is about 2:1. Compared with individual micron-silver or nano-silver, mixed silver pastes can achieve higher densification and shear strength. However, in order to obtain the desired properties, the sintering temperature of the mixed silver paste must be higher than 300°C and the sintering pressure must be greater than 2MPa.

[0015]

[0006] Therefore, there is a need for compositions and composites that alleviate one or more of the above-mentioned disadvantages. Summary of the invention

[0016] In one aspect, a composition is provided, comprising a deoxidizer solvent, a cosolvent, and a plurality of silver particles suspended in the mixture of the deoxidizer solvent and the cosolvent,

[0017] The deoxidizer solvent comprises one or more of formula C n O m H 2n+2-p (OH) p wherein n, m and p are integers, provided that 1≤(n+m) / p≤8, and

[0018] The mixture of the deoxidizer solvent and the co-solvent contains hydroxyl groups at a concentration of 2M to 20M.

[0019] In another aspect, a method of forming a composition is provided, the method comprising the step of dispersing a plurality of silver particles in a deoxidizer solvent in the presence of a cosolvent or in a mixture of a deoxidizer solvent and a cosolvent.

[0020] In another aspect, there is provided a method of forming a composite material, the method comprising the step of sintering the composition described herein on a substrate.

[0021] Advantageously, the composition does not require air or oxygen to "burn off" excess organic matter during the sintering step. Therefore, the composition is compatible with copper and aluminum interconnects that may be present on the die. This is because any organic polymer used is only present in small amounts at the surface of the silver particles.

[0022] Advantageously, the sintering of the composition does not require a cumbersome reducing atmosphere because the deoxidizer solvent and co-solvent provide the chemical reagents required to reduce the silver oxide.

[0023] More advantageously, the sintering of the composition does not require high pressure. Therefore, the method does not require expensive pressure conversion equipment. This improves the reliability of the die or substrate to which the composite material is attached. This advantage stems from the more efficient sintering achieved by the method of the present invention.

[0024] In one example, the sintering temperature is less than 200°C.

[0025] Advantageously, when the sintering temperature is lower than 200° C., the composition can decompose or reduce native silver oxide to a higher degree.

[0026] In another aspect, a device is provided, the device comprising a composite material formed by the methods described herein.

[0027] definition

[0028] As used herein, the following words and terms shall have the meanings indicated:

[0029] The wording "substantially" does not exclude "completely", for example, a composition "substantially free" of Y may be completely free of Y. If desired, the word "substantially" may be omitted from the definition of the present invention.

[0030] Unless otherwise stated, the term "comprise" and its grammatical variations are intended to represent an "open" or "inclusive" expression such that they include the listed elements but also allow for additional, non-listed elements.

[0031] As used herein, the term "about" generally means + / - 10% of the stated value or 1 unit in the last digit of the stated value, whichever is greater.

[0032] In the present disclosure, certain embodiments may be disclosed in a range format. It should be understood that the description in a range format is only for the purpose of convenience and brevity, and should not be interpreted as constituting a hard limit to the disclosed range. Therefore, the description of the range should be deemed to specifically disclose all possible sub-ranges and each numerical value within the range. For example, the description of a range such as 1 to 6 should be deemed to specifically disclose sub-ranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, and each number within the range, such as 1, 2, 3, 4, 5, and 6. This applies regardless of the breadth of the range.

[0033] Certain embodiments may also be described herein in a broad and general manner. Each of the narrower classes and subgeneric groupings within the general disclosure also form part of this disclosure. This includes the general description of embodiments with a proviso or negative limitation removing any subject matter from the class, regardless of whether the removed material is specifically recited herein. DETAILED DESCRIPTION

[0034] An exemplary, non-limiting embodiment of a composition will now be disclosed.

[0035] The composition comprises a deoxidizer solvent, a cosolvent, and a plurality of silver particles suspended in the mixture of the deoxidizer solvent and the cosolvent.

[0036] The deoxidizer solvent comprises one or more of formula C n O m H 2n+2-p (OH) p wherein n, m and p are integers, provided that 1≤(n+m) / p≤8, and

[0037] The mixture of the deoxidizer solvent and the co-solvent contains hydroxyl groups at a concentration of 2M to 20M.

[0038] Advantageously, the composition can be prepared to have a thermal conductivity of at least about 1.0×10 5 S / cm and a thermal conductivity of at least about 75 W / mK.

[0039] The combined weight percent of the deoxidizer solvent and the co-solvent can be about 6 weight percent to about 30 weight percent, about 12 weight percent to about 25 weight percent, or about 18 weight percent to about 25 weight percent based on the total weight of the composition.

[0040] The volume ratio of the deoxidizer solvent to the co-solvent may be about 1:1.0 to about 1:10 or about 1:1.0 to about 1:5.

[0041] Advantageously, when present in diluted form, the deoxidizer solvent is able to avoid the formation of bubbles during sintering of the composition.

[0042] The average diameter of the plurality of silver particles may be about 0.2 μm to about 20 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 15 μm to about 20 μm, about 0.2 μm to about 15 μm, about 0.2 μm to about 10 μm, or about 0.2 μm to about 5 μm.

[0043] The size distribution of the plurality of silver particles (i.e., 16% to 84% of the cumulative distribution by mass) as measured by particle size analysis (e.g., laser scattering) can range from about ±10% (i.e., narrow dispersion) to about ±70% (i.e., broad dispersion), from about ±20% to about ±70%, from about ±50% to about ±70%, from about ±10% to about ±50%, or from about ±10% to about ±20% of the average diameter.

[0044] The size distribution may be unimodal, bimodal or multimodal.

[0045] Where the size distribution is bimodal, the size distribution can have a size ratio of about 10:3 to about 10:0.3, about 10: 1.0 to about 10:0.3, or about 10:3 to about 10: 1.0.

[0046] Where the size distribution is multimodal, the size distribution may have a size ratio of about 10:3:1.0.

[0047] Advantageously, the size distribution as described above makes the plurality of silver particles particularly suitable for the composition of the present invention because the plurality of silver particles includes smaller particles and larger particles, wherein the smaller particles can fill the spaces between the larger particles.

[0048] The plurality of silver particles may be in the form of flakes, granules, spheres, or a combination thereof.

[0049] The plurality of silver particles may be in the form of flakes. Advantageously, the flake form can provide a composite material made from the composition with lower final porosity, better conductivity and adhesion properties than other forms.

[0050] In the case where the plurality of silver particles are in the form of flakes, the plurality of silver particles may have a size of about 0.6 μm. 2 / g to about 2.5m 2 / g, about 1m 2 / g to about 2.5m 2 / g, about 2m 2 / g to about 2.5m 2 / g, about 0.6m 2 / g to about 2m 2 / g or about 0.6m 2 / g to about 1.0m 2 The specific surface area (i.e., exposed surface area per unit mass) of the silver particles is 1.3447 W / g. The specific surface area can be measured by gas adsorption as the BET surface area. Therefore, the specific surface area can be determined by the preparation method of the plurality of silver particles (e.g., by a grinding process).

[0051] In the case where the plurality of silver particles are in a spherical form and have an average diameter of about 2 μm, the specific surface area of ​​the plurality of silver particles may be about 0.3 m2 / g.

[0052] As the specific surface area decreases, multiple silver particles can have higher stiffness.

[0053] The plurality of silver particles may have a volume of at least about 2.5 g / cm 3 or at least about 3.5 g / cm 3 The tap density of the plurality of silver particles is the ratio of the total mass of the plurality of silver particles to the total volume occupied by the plurality of silver particles after the plurality of silver particles are tapped to a constant volume.

[0054] The plurality of silver particles may include elemental silver particles, silver alloy particles, silver-coated particles, silver oxide particles, or a combination thereof.

[0055] The silver coated particles may be silver coated copper particles.

[0056] The composition may also include a silver additive. Non-limiting examples of silver additives include silver-coated silicon dioxide, silver-coated silicon carbide, silver-coated boron nitride, silver-coated ceramic oxides, silver-coated glass, silver oxide, or a combination thereof. Advantageously, the presence of the silver additive can provide a composite material made from the composition with higher mechanical strength.

[0057] As described above, (n+m) / p represents the number of hydroxyl groups. A deoxidizer solvent having a small number of hydroxyl groups (e.g., about 1 to about 2) has a high concentration of hydroxyl groups, so a small amount (by mass) of the deoxidizer solvent can be used to achieve the deoxidation effect. However, such a deoxidizer solvent also tends to produce a violent reaction that produces bubbles during deoxidation, which is undesirable because the bubbles expand the composite material during sintering. Due to the generation of bubbles, the composite material made from the composition may have lower conductivity and mechanical strength, so it is necessary to dilute the deoxidizer solvent.

[0058] In the case where the deoxidizer solvent has a larger hydroxyl number (eg, about 5 to about 8), a larger amount (by mass) of the deoxidizer solvent is required to achieve the deoxidation effect, and the deoxidation can be performed more slowly and steadily.

[0059] Advantageously, it is convenient and inexpensive to control the deoxygenation of the composition by adjusting the deoxygenator solvent as needed.

[0060] The deoxidizer solvent may have a boiling point of about 190°C to about 350°C, about 250°C to about 350°C, about 300°C to about 350°C, about 190°C to about 300°C, or about 190°C to about 250°C.

[0061] Advantageously, when the deoxidizer solvent has a boiling point as described above, the deoxidizer solvent will have a sufficiently low vapor pressure so as to remain substantially with the composition during deoxidation of the composition. Specifically, deoxidation of the composition occurs at a deoxidation temperature, which is the lowest temperature at which the plurality of silver particles can be reduced at an appreciable reduction rate. The deoxidation temperature can be estimated in a variety of ways, such as by reacting bulk silver oxide powder with a presumed deoxidizer solvent at a low heating rate (e.g., 2° C. per minute).

[0062] More advantageously, since the deoxidizer solvent is in liquid form, it can be completely removed by drying (e.g., annealing for a longer time, annealing at a higher temperature, annealing under vacuum conditions, or a combination thereof) without leaving any residues that would cause undesirable corrosion or other deficiencies in the composite material made from the composition. Therefore, the deoxidizer solvent is more effective than a solid form of deoxidizer or reducing agent that is not easily removed by a drying step.

[0063] If the deoxidizer solvent is lost in large quantities (e.g., by evaporation) before the deoxidation temperature is reached, the deoxidizer solvent will be ineffective. As described above, the boiling point of the deoxidizer solvent provides an indication of its vapor pressure at lower temperatures. The inventors have found that certain deoxidizer solvents have a significant evaporation rate (e.g., on the order of about 2 microns / minute) at temperatures about 100° C. below their boiling points.

[0064] Thus, for interconnect applications, the boiling point of the deoxidizer solvent may be at least about 100°C or about 150°C higher than the deoxidation temperature where the evaporation rate does not adequately attenuate the composition for a desired printing or dispensing pattern because the deposited composition is exposed and not covered by other features.

[0065] Alternatively, for thermal interface, die attach, and other bonding applications, the deoxidizer solvent may evaporate only along the edge (e.g., of the die), and the evaporation rate may depend on the size of the die. Therefore, for these applications, the boiling point of the deoxidizer solvent may be lower, such as about 50°C higher than the deoxidation temperature. If the composition is to be subjected to a pre-drying treatment, the temperature of the pre-drying treatment may be at least about 100°C or about 150°C lower than the boiling point of the deoxidizer solvent.

[0066] The deoxidizer solvent may be present in an amount calculated according to the reaction stoichiometry. The theoretical specific amount of hydroxyl groups (N) required per unit mass of the plurality of silver particles may be derived from the specific surface area (S) of the plurality of silver particles, the thickness (d) of the plurality of silver particles, the density (ρ) of the plurality of silver particles, the molecular weight (M) of the plurality of silver particles, and the stoichiometric number (ξ) of the plurality of silver particles according to the following equation:

[0067] N=S×d×ρ / (M×ξ)

[0068] Assuming that each hydroxyl group acts as a two-electron reducing agent (i.e., reducing one formula unit of Ag2O to Ag), then multiple silver particles can have 2×10 -9 m thickness (d), 7.14×10 6 g / m 3 The stoichiometry (ξ) of 1 is 2. In fact, the primary hydroxyl group can act as a four-electron reducing agent, which changes the stoichiometry (ξ) to 2.

[0069] Therefore, the plurality of silver particles has a size of about 0.6 μm. 2 / g to about 2.5m 2 In the case of silver flakes with a specific surface area (S) of 1.50 μmol / g, the theoretical specific hydroxyl amount (N) calculated according to the above equation is about 35 μmol / g to about 150 μmol / g. The inventors have found that this theoretical specific hydroxyl amount (N) is sufficient to complete deoxidation. Alternatively, the deoxidizer solvent may be present in an amount up to four times the theoretical amount to compensate for the loss (e.g., evaporation) of the deoxidizer solvent during processing.

[0070] Non-limiting examples of deoxidizer solvents include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, isomers of propylene glycol, isomers of butanediol, isomers of pentanediol, isomers of hexanediol, isomers of heptanediol, isomers of octanediol, glycerol, pentaerythritol, dipentaerythritol, 2-(2-methoxyethoxy)ethanol, 2-(2-ethoxyethoxy)ethanol, and combinations thereof.

[0071] Surprisingly, the above deoxidizer solvent is a strong deoxidizer for bulk silver oxide powder Ag2O at low temperatures (e.g., about 130°C). Therefore, the deoxidizer solvent can advantageously promote the sintering of the composition as a deoxidizer.

[0072] More advantageously, when present in a diluted form, the deoxidant solvent is able to avoid the formation of bubbles during sintering of the composition thereby limiting the activity of the deoxidation reaction.

[0073] The deoxidizer solvent and the co-solvent are miscible in each other when combined to form a homogeneous mixture.

[0074] The boiling point of the co-solvent can be about 60°C to about 350°C, about 100°C to about 350°C, about 200°C to about 350°C, about 300°C to about 350°C, about 60°C to about 300°C, about 60°C to about 200°C, or about 60°C to about 100°C.

[0075] Advantageously, the co-solvent can determine the rheology of the composition together with the plurality of silver particles and the deoxidizer solvent. The co-solvent can also improve the sintering characteristics of the composition. The co-solvent can further improve the shelf life, pot life and working life of the composition.

[0076] A co-solvent may have one or more of the following functions:

[0077] (i) The low boiling point co-solvent acts as a diluent or carrier solvent to improve the rheology of the composition to obtain a desired concentration of a plurality of silver particles.

[0078] (ii) The high boiling point co-solvent can improve the metal filling factor of a composite material made from the composition by diluting the deoxidizer solvent to an optimum concentration for a smooth deoxidation reaction.

[0079] (iii) The high boiling point co-solvent can improve the bonds formed between the plurality of silver particles. The co-solvent can also improve the bonds formed between the composite material made from the composition and other surfaces. In this function, the co-solvent acts as a sintering aid, wetting agent or co-deoxidizer solvent at the deoxidation temperature set by the deoxidizer solvent, thereby improving the conductivity and cohesive / adhesive strength of the composite material made from the composition.

[0080] In the case where the co-solvent acts as a carrier solvent to be evaporated during the pre-drying process of the deoxidizer solvent, the boiling point of the co-solvent can be at least about 40°C or 80°C lower than the boiling point of the deoxidizer solvent. Advantageously, the lower boiling point co-solvent can improve the density of the composition during the pre-drying process before sintering the composition. The improved density provides better performance for thermal interface and die attach applications and for producing laminates from the composition on plastic carrier films.

[0081] The deoxidizer solvent, cosolvent or mixture thereof can contain hydroxyl groups at a concentration of about 2M to about 20M, about 2M to about 14M, about 4M to about 14M or about 6M to 14M. Both the deoxidizer solvent and the cosolvent can contribute to the total hydroxyl concentration as long as the final concentration of the hydroxyl group falls within the above range. At the above concentration, the composition can be advantageously sintered smoothly. This concentration can reduce the formation of bubbles, thereby reducing the expansion of the composite material made of the composition.

[0082] Additionally or alternatively, in the case where the co-solvent acts as a co-deoxidant solvent, the co-solvent may contain polarizable groups, such as alkenyl, aryl, carbonyl, ether, etc. Advantageously, the polarizable groups may help to transfer Ag(I) ions and / or silver atoms from the local dissolution site of silver to the local deposition site, especially at the junction (e.g., neck region or bridging region) as described above. In addition, the co-solvent is able to induce Ag2O powder to form a silver mirror on the glass surface at a mild temperature (e.g., about 130°C) without substantially reducing the Ag2O powder. Therefore, the co-solvent may act as a co-deoxidant solvent, which may promote the transport of metal atoms or ions across the co-solvent, thereby enhancing the sintering of the composition. Since the co-solvent may act as a co-deoxidant solvent, the co-solvent may continue to exist at the deoxidation temperature. Accordingly, at this, the boiling point of the co-solvent may be similar to or higher than the boiling point of the deoxidant solvent as described above. Also for this purpose, the co-solvent may act as a wetting solvent for the deoxidant solvent.

[0083] Non-limiting examples of co-solvents include xylene isomers, mesitylene, tetralin, terpinene, limonene, linalool, α-terpineol, geraniol, citronellol, diethylene glycol dimethyl ether, 1,2-dibutoxyethane, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, diethylene glycol butyl ether, tripropylene glycol methyl ether, triethylene glycol ethyl ether, triethylene glycol butyl methyl ether, triethylene glycol butyl ether, propylene glycol methyl ether, sulfolane, 2-(2-butoxyethane)-1,2-dibutoxyethane, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, diethylene glycol butyl ether, tripropylene glycol methyl ether, triethylene glycol ethyl ether, triethylene glycol butyl methyl ether, triethylene glycol butyl ether, propylene glycol methyl ether, cyclopentane, 2-(2-butoxyethane)-1,2-dibutoxyethane, di ... 2-(Benzyloxy)ethanol, phenoxyethanol, 2-(Benzyloxy)ethanol, di(propylene glycol)methyl ether, 2-butoxyethanol acetate, ethylene glycol diacetate, propylene glycol methyl ether acetate, di(propylene glycol)methyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, ethylene glycol monobutyl ether acetate, 2-ethoxyethyl acetate, ethylene glycol monoethyl ether acetate, 2-butoxyethyl acetate, ethanolamine, diethanolamine, Texanol TM Ester alcohol, diethyl adipate, dimethyl succinate, methyl benzoate, N-methylpyrrolidone, gamma-butyrolactone, diethyl carbonate, propylene carbonate, safrole, anethole, cyclohexanone, cyclohexanol, carvone, ethyl sorbate, pseudoionone, farnesene, 2,6-dimethyl-2,4,6-octatriene, o-cresol, methyl salicylate, and combinations thereof.

[0084] The co-solvent and deoxidizer solvent may be selected to provide a composition having a viscosity of about 500 cP to about 500,000 cP, about 5,000 cP to about 50,000 cP, about 50,000 cP to 500,000 cP, or about 500 cP to about 5,000 cP to have a desired rheology. The viscosity may be measured at a speed of about 5 revolutions per minute.

[0085] The co-solvent and deoxidizer solvent may be selected to provide the composition with a thixotropic index of about 3 to about 8, about 5 to about 8, or about 3 to about 5 to have the desired rheology. The thixotropic index may be measured at a rate of about 0.5 to about 5 revolutions per minute.

[0086] The composition may also include a modifier polymer.

[0087] Polymers are often used as binders to fill the gaps between metal particles and improve the adhesion between the metal particles and the substrate. Typical polymers are macromolecules with a molecular weight of more than about 1 kDa and more than 10 repeating units bonded together. The polymer is usually included in the composition in a volume ratio of about 20:100 to about 50:100 relative to the metal particles. However, typical polymers severely hinder the sintering of metal particles and limit the electrical and thermal conductivity of the sintered metal particles.

[0088] Unexpectedly, certain classes of polymers can be advantageously used as modifier polymers to form a molecularly thick coating on the surface of a plurality of silver particles. The coating can have a thickness of about 3.5 nm to about 9 nm, about 5.5 nm to about 9 nm, about 7 nm to about 9 nm, about 3.5 nm to about 7 nm, or about 3.5 nm to about 5.5 nm.

[0089] The modifier polymer may have one or more of the following functions:

[0090] (i) Modifier polymers can improve the rheology and dispersibility of the composition by preventing the aggregation of multiple silver particles.

[0091] (ii) The modifier polymer is capable of improving the adhesion between the plurality of silver particles and a non-metallized surface (eg, the surface of a semiconductor, oxide, or plastic substrate).

[0092] (iii) Modifier polymers can act as sintering aids to improve the sintering of the composition by reducing the sintering temperature required to sinter the composition and improving the conductivity of composite materials made from the composition.

[0093] The modifier polymer may contain hydrogen bonding groups, polarizable groups, acidic groups, basic groups, other polar groups, or combinations thereof. The modifier polymer may contain glycol ethers (-CH2CH2O-), acetals (-OCRR'O-), amines (-R"NH2, -R"N(H)R"-, -R"N(R)R"'-), side chain amides (-C(=O)NH-, -C(=O)N(R)-), ureas (-NH(C=O)NH-), hydroxyls (-OH), carboxylates (-COOH), carboxylates (-COO - M + ), sulfonic acid (-SO3H), sulfonate (-SO3 –M + ), phosphonic acid (–PO3H2), phosphonates (–PO3H – M + ), olefins (-C(R)=C(R')-), aromatic groups, or combinations thereof, wherein R, R', R" and R"' are independently H or organic moieties. R and R' can be methyl or ethyl. R" and R"' can be C1-C6 alkylene or C6-C 10 Arylene (eg, phenylene or naphthylene).

[0094] Hydrogen bonding groups, polarizable groups, acidic groups, basic groups and other polar groups can be independently present on the main chain, block chain, side chain or grafted chain of the modifier polymer. The modifier polymer can be bound to the Ag / Ag2O surface or the non-metallized surface as described above.

[0095] In the case where the modifier polymer comprises glycol ether (–CH2CH2O–), acetal (–OCR'R”O–), amine (–R”NH2, –R”N(H)R”'–, –R”N(R')R”'–), side chain amide (–C(=O)NH–, –C(=O)N(R)–), urea (–NH(C=O)NH–), hydroxyl (–OH), olefin (-C(R)=C(R')-), aromatic group or a combination thereof (wherein R, R' and R” are independently H or an organic moiety), the modifier polymer is capable of promoting the transport of metal atoms or ions on the surface of multiple metal particles, thereby accelerating the formation of junctions (e.g., bridge contacts and neck regions) between adjacent silver particles and the coarsening of the neck region.

[0096] The modifier polymer can be thermally stable when a device made from the composition is used. The modifier polymer can be thermally stable up to at least about 300° C. as determined by thermogravimetric analysis.

[0097] Non-limiting examples of modifier polymers include poly(ethylene oxide), polyethylene imine (ethoxylated and non-ethoxylated), polyaniline, polypyrrole, poly(3,4-ethylenedioxythiophene), poly(lysine), poly(arginine), poly(histidine), poly(acrylic acid), poly(methacrylic acid), poly(aspartic acid), poly(glutamic acid), polyacrylamide, polyvinylpyrrolidone, poly(acrylamido-2-methyl-1-propanesulfonic acid), poly(vinylsulfonic acid), poly(styrenesulfonic acid), poly(vinylphosphonic acid), , poly(dopamine), dextran, carboxymethyl cellulose, alginate, poly(serine), poly(2-hydroxyethyl methacrylate), poly(vinyl alcohol) (40–97% hydrolyzed), poly(vinyl butyral) and poly(hydroxystyrene) and their salts (if applicable); doped conductive polymers including poly(ethylenedioxythiophene), poly(styrenesulfonic acid), poly(thiophene-3-[2-(2-methoxyethoxy)ethoxy]-2,5-diyl) and poly(triarylammonium-alt-fluorene) and their derivatives.

[0098] Because the modifier polymer does not act as a binder like a typical polymer, the modifier polymer can be present in a lower amount in the composition than a typical polymer. For example, the modifier polymer can be present in a specific amount per unit mass of the plurality of silver particles (P), the specific amount being derived from the specific surface area (S) of the plurality of silver particles, the nominal thickness (d) of the modifier polymer, and the density (ρ) of the modifier polymer by the following formula:

[0099] P=S×d×ρ

[0100] The modifier polymer may have a 6 g / m 3 The nominal thickness (d) of the modifier polymer may be about 3.5×10 -9 μm to about 9×10 -9 μm, about 6×10 -9 μm to about 9×10 -9 μm or about 3.5×10 -9 μm to about 6×10 -9 μm.

[0101] Therefore, the plurality of silver particles is about 1.6 μm 2In the case of silver flakes with a specific surface area (S) of 100 g / g, the weight ratio of the modifier polymer to the plurality of silver particles can be about 0.6:100 to about 1.6:100, about 1.1:100 to about 1.6:100, or about 0.6:100 to about 1.1:100. The above weight ratios can correspond to the volume ratios of the modifier polymer to the plurality of silver particles, i.e., about 6:100 to about 15:100, about 10:100 to about 15:100, or about 6:100 to about 10:100. Advantageously, as described above, the above weight ratios and volume ratios are significantly lower than those of typical polymers.

[0102] The plurality of silver particles are present in an amount of about 65 weight percent to about 94 weight percent based on the total weight of the composition and have a thickness of about 1.0 m 2 / g to about 2.2m 2 In the case of a specific surface area of ​​100 to 200 g, the modifier polymer may be present at a weight percentage of about 0.3 weight percent to about 1.9 weight percent based on the total weight of the composition (or, at a weight percentage of about 0.4 weight percent to about 2 weight percent based on the total weight of the plurality of silver particles). In the case where the plurality of silver particles are silver-coated particles (e.g., silver-coated copper particles), the modifier polymer may be present at a similar weight percentage because the silver-coated particles may have a density similar to that of silver.

[0103] The composition may also contain a reducing metal.

[0104] The reducing metal may include aluminum, magnesium, chromium, manganese, or combinations thereof.

[0105] The reducing metal may be present in a weight percent of up to about 2.0 weight percent or about 1.0 weight percent based on the total weight of the composition.

[0106] The reducing metal may have an average diameter similar to an average diameter of the plurality of silver particles.

[0107] Advantageously, the reducing metal can reduce the native oxides on the silver particles and silver additives and other metal oxides on the die or substrate by reacting with the deoxidizer solvent and / or water at the sintering temperature, thereby producing a lower and safe concentration of nascent hydrogen. This hydrogen can be released and can reduce the remaining silver oxide and other metal oxides on the surface of the substrate or die.

[0108] Exemplary, non-limiting embodiments of methods of forming the compositions will now be disclosed.

[0109] The method includes the steps of dispersing a plurality of silver particles in a deoxidizer solvent in the presence of a cosolvent or dispersing a plurality of silver particles in a mixture of a deoxidizer solvent and a cosolvent.

[0110] The plurality of silver particles, the deoxidizer solvent, and the co-solvent may be as described herein.

[0111] The method may further include the step of treating the plurality of silver particles with a modifier polymer.

[0112] In the case where the modifier polymer is substantially soluble in the deoxidizer solvent and / or co-solvent, the treating step may be performed after the dispersing step. The treating step may include dissolving the modifier polymer in the composition and mixing the composition. Thus, the method may include the following steps:

[0113] a) dispersing a plurality of silver particles in a deoxidizer solvent in the presence of a co-solvent to form a dispersion;

[0114] b) dissolving a modifier polymer in the dispersion; and

[0115] c) mixing the dispersions to form a composition.

[0116] The mixing step (c) can be performed by shear mixing or ultrasonic treatment. During the mixing step, the modifier polymer can spontaneously exchange with the protective molecular monolayer or other processing aids on the surface of the plurality of silver particles. The exchange can also occur when the composition formed by the method is sintered.

[0117] Alternatively, when the modifier polymer is substantially insoluble in the deoxidizer solvent and / or co-solvent, the treating step may be performed prior to the dispersing step. The treating step may include dissolving and mixing the modifier polymer and a plurality of silver particles in an exchange solvent, followed by separation of the plurality of silver particles. Thus, the method may include the following steps:

[0118] a) dissolving a plurality of silver particles and a modifier polymer in an exchange solvent to form a dispersion;

[0119] b) mixing the dispersion;

[0120] c) separating a plurality of silver particles from the dispersion; and

[0121] d) dispersing a plurality of silver particles in a deoxidizer solvent in the presence of a co-solvent to form a composition.

[0122] In the dissolving step (a), the exchange solvent may have good solubility for the protective molecular monolayer or other processing aid on the surface of the plurality of silver particles. The exchange solvent may have relatively low solubility for the modifier polymer. To determine whether the dissolving step has been successfully performed, the dispersion of step (a) may be characterized by surface analysis techniques (e.g., X-ray photoemission spectroscopy).

[0123] The mixing step (b) may be performed by shear mixing or ultrasonic treatment.

[0124] The mixing step (b) may be conducted at a temperature of about 20°C to about 100°C, about 60°C to about 100°C, or about 20°C to about 60°C.

[0125] During the mixing step (b), the modifier polymer may spontaneously exchange with the protective molecular monolayer or other processing aid on the surface of the plurality of silver particles.

[0126] The separation step (c) can be performed by filtration or centrifugation.

[0127] The separation step (c) may further comprise rinsing the plurality of silver particles with a rinse solvent to remove excess modifier polymer that was not bound to the plurality of silver particles during the mixing step. The rinse solvent may have a low boiling point so that they are easily removed. The rinse solvent may be ethanol, isopropanol, or a combination thereof.

[0128] The separation step (c) may further comprise drying the plurality of silver particles. The exchange solvent and the rinse solvent (if present) may be removed from the plurality of silver particles by drying. The plurality of silver particles may then be used in the dispersion step (d) to form a composition.

[0129] In the plurality of silver particles having a size of about 1.0 μm 2 / g to about 2.2m 2 In the case of a specific surface area of ​​100 wt % to 50 wt % , the plurality of silver particles may contain about 98 wt % to about 99.6 wt % of silver particles and about 0.4 wt % to about 2 wt % of the modifier polymer, based on the total weight of the plurality of silver particles after the treating step.

[0130] The compositions as described herein can be formed by the methods as described herein.

[0131] Exemplary, non-limiting embodiments of methods of forming composite materials will now be disclosed.

[0132] The method comprises the step of sintering a composition as described herein on a substrate.

[0133] Advantageously, the composition does not require air or oxygen to "burn off" excess organic matter during the sintering step. Therefore, the composition is compatible with copper and aluminum interconnects that may be present on the die. This is because any organic polymer used is only present in small amounts at the surface of the silver particles.

[0134] Advantageously, the sintering of the composition does not require a cumbersome reducing atmosphere because the deoxidizer solvent and co-solvent provide the chemical reagents required to reduce the silver oxide.

[0135] More advantageously, the sintering of the composition does not require high pressure. Therefore, the method of the present invention does not require expensive pressure conversion equipment. This improves the reliability of the die or substrate to which the composite material is attached. This advantage stems from the more efficient sintering achieved by the method of the present invention.

[0136] The sintering step may be performed at a temperature of about 200° C. or less. The sintering step may be performed at a temperature of about 140° C. to about 180° C. or about 150° C. to about 180° C. The temperature may be set and / or monitored by a digital hot plate or oven.

[0137] Advantageously, when the sintering temperature is below 200°C, the composition can have a higher degree of decomposition or reduction of native silver oxide.

[0138] The sintering step may be performed in an inert atmosphere. The sintering step may be performed in nitrogen.

[0139] Advantageously, the sintering step may transform the composition into a dense and substantially fused agglomerated metal powder without microscopic voids or polymer phases.

[0140] The method may further comprise the step of pre-drying the composition prior to the sintering step.

[0141] The method may further comprise the step of contacting the composition with a second substrate or component prior to the sintering step.

[0142] The contacting step can be performed by depositing the composition onto a second substrate or component. The deposition of the composition can be performed using various printing and coating techniques, such as needle dispensing, doctor blade coating, template printing, screen printing, gravure printing or flexographic printing, etc. In the case where the composition is deposited onto the substrate and the second substrate or component simultaneously, the method may include the following steps:

[0143] a) depositing a composition as described herein onto a substrate and a second substrate or component; and

[0144] b) Sintering the composition.

[0145] Alternatively, the composition may be deposited on one or more substrates in sequence. Thus, the method may comprise the following steps:

[0146] a) depositing a composition as described herein onto a substrate;

[0147] b) pre-drying the composition to form a laminate;

[0148] c) contacting the laminate with a second substrate or component; and

[0149] d) Sintering the laminate.

[0150] The substrate may be a plastic film.

[0151] The pre-drying step (b) may be carried out at a temperature lower than the temperature of the sintering step (d). The pre-drying step (if present) may be carried out before the contacting step (if present).

[0152] The second substrate or component may be a device, a wafer, or a die.

[0153] Advantageously, the pre-drying step (b) can reduce the processing time of the second substrate or component, provide good control over the thickness of the laminate, and allow for greater processing flexibility.

[0154] In the contacting step (c), the second substrate or component may be selected from electronic components and thermal components.

[0155] Thus, after the sintering step, the composite material may bond the substrate and the second substrate or component. The composite material together with the substrate and the second substrate or component may be considered as a device.

[0156] Therefore, the method can be considered as a method of manufacturing a device for connecting vertical electronic or thermal components. In the device, the composite material can be sandwiched between a first electronic component and a second electronic or thermal component.

[0157] Alternatively or additionally, the method may be viewed as a method of manufacturing a device for connecting lateral electronic or thermal components or for connecting different regions of an electronic or thermal component. In the device, the composite material may be formed in a lateral pattern to join the electronic or thermal component or different regions of the electronic or thermal component.

[0158] Advantageously, the composite materials can be used as electrically and thermally conductive materials, such as thermal interfaces, die attach, electrical interconnects, or electrode materials.

[0159] In the case where the composite material is used as a thermal interface material, it can provide thermal contact between the semiconductor chip and the heat sink.

[0160] Where the composite material is used as a die attach material, it may bond the chip to a substrate or packaging material, thereby also providing electrical and / or thermal contact.

[0161] Where the composite material is used as a thermal interface material or a die attach material, it may be fabricated to have a thickness of about 10 μm to about 500 μm, about 50 μm to about 500 μm, about 200 μm to about 500 μm, about 10 μm to about 200 μm, about 10 μm to about 50 μm, or about 50 μm to about 200 μm.

[0162] Where the composite material is used as an electrical interconnect material or electrode material, it can provide contacts, bus bars, antennas and wiring, such as in solar cells, switches, capacitors, sensors and other components of printed electronics. The composite material can be manufactured to a thickness of about 100 nm to about 10 μm, about 1.0 μm to about 10 μm, or about 100 nm to about 1 μm.

[0163] Where the composite material is deposited on a device or substrate, the composite material can be manufactured to have a width of about 10 μm to about 1.0 mm, about 100 μm to about 1.0 mm, or about 10 μm to about 100 μm. The composite material can have a length of about 10 μm to about 10 m, about 100 cm to about 10 m, about 1.0 m to about 10 m, about 10 cm to about 1.0 m, or about 10 cm to about 100 cm.

[0164] In the case where the composite material is deposited on a heat generating device or a related substrate, it can be manufactured to have a length of about 10 mm to about 1.0 cm, about 100 mm to about 1.0 cm, or about 10 mm to about 100 mm. The composite material can be manufactured to have a width of about 10 mm to about 1.0 cm, about 100 mm to about 1.0 cm, or about 10 mm to about 100 mm.

[0165] The composite material may be used without a substrate. Therefore, the method may further comprise the step of removing the substrate.

[0166] Exemplary, non-limiting embodiments of composite materials will now be disclosed.

[0167] The composite material may be prepared by the methods described herein. Thus, the composite material may comprise dense and substantially fused agglomerated metal powders without microscopic voids or polymer phases.

[0168] Composite materials can be used to transmit electrical current and / or heat flow across connected electronic components.

[0169] Advantageously, the composite material may have a 5 S / cm and a thermal conductivity of at least about 75 W / mK.

[0170] Exemplary, non-limiting embodiments of the apparatus will now be disclosed.

[0171] The device can be prepared by the methods as described herein.

[0172] Thus, a device may comprise a composite material formed by a method as described herein.

[0173] The device may be an electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0174] The accompanying drawings illustrate the disclosed embodiments and are used to explain the principles of the disclosed embodiments. However, it should be understood that these drawings are designed only for illustrative purposes and are not intended to limit the present invention.

[0175] Figure 1A

[0176] Figure 1A is a scanning electron micrograph (SEM) of a cross-section of an exemplary composite material made according to the present application. Figure 1A The scale bar is 10 μm.

[0177] Figure 1B

[0178] Figure 1B is a SEM of a cross section of an exemplary composite material made according to the present application. Figure 1B The scale bar is 10 μm.

[0179] Figure 1C

[0180] Figure 1C is a SEM of a cross section of an exemplary composite material made according to the present application. Figure 1C The scale bar is 10 μm.

[0181] Figure 1D

[0182] Figure 1D is a SEM of a cross section of an exemplary composite material made according to the present application. Figure 1D The scale bar is 10 μm.

[0183] Figure 1E

[0184] Figure 1E is a SEM of a cross section of an exemplary composite material made according to the present application. Figure 1E The scale bar is 10 μm.

[0185] Figure 1F

[0186] Figure 1F is a SEM of a cross section of an exemplary composite material made according to the present application. Figure 1F The scale bar is 10 μm.

[0187] Example

[0188] The non-limiting embodiments of the present invention will now be further described in detail by reference to specific examples, which should not be interpreted as limiting the scope of the present invention in any way. The actual performance depends on the properties of the particles, the details of preparation, the processing and the application method. In some cases, vibration and centrifugation are used to increase the metal filling factor.

[0189] Example 1 - Preparation of paste using silver flakes and modifier polymer

[0190] The following examples show pastes with silver flakes and modifier polymers prepared by first dissolving the modifier polymer into a solvent system and then mixing with metal powder. Silver flakes and silver spheres as used herein can be obtained from commercial sources such as Heraeus, Hitachi, Henkel, Inframat Advanced Materials, ACS Material, Fukuda Metal Foil & Powder, Hongwu Material Tech, Tanaka Precious Metals, Johnson Matthey, DuPont, Technic, Doduco, Yamamoto Precious Metal, Mitsui Kinzoku, Ningbo Jingxin, Changgui Metal Powder, and American Elements.

[0191] Example 1a

[0192] 0.22 mL of poly(hydroxystyrene) (purchased from Sigma-Aldrich, Singapore) dissolved at a polymer concentration of 54 mg / mL in a mixture of diethylene glycol dimethyl ether (purchased from Sigma-Aldrich, Singapore), glycerol (purchased from Sigma-Aldrich, Singapore) and ethylene glycol (purchased from Sigma-Aldrich, Singapore) (6.0:0.5:1.5 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 3 to 5 μm; tap density = 2.8 to 3.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.3m 2 / g) to obtain a paste containing 81.7 weight percent silver, 1.0 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2The paste was pre-dried at 60°C in air for 20 minutes, affixed with fluoropolymer-coated glass (purchased from Sigma-Aldrich, Singapore), and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at this temperature for 30 minutes.

[0193] Figure 1A is a SEM of a cross section of the bulk portion of a 130 μm thick metal composite of silver flakes (average size of about 3 to 5 μm) as described in Example 1a using 1.0 weight percent poly(hydroxystyrene). The metal composite was formulated with diethylene glycol dimethyl ether, glycerol, and ethylene glycol in a volume ratio of 6.0:0.5:1.5 and pressurelessly sintered at 160°C in nitrogen for 30 minutes.

[0194] Figure 1B yes Figure 1A SEM of the cross section at the interface between the metal composite and native SiO2 / Si shown in FIG.

[0195] Example 1b

[0196] 0.22 mL of 40% hydrolyzed polyvinyl alcohol (purchased from Mitsubishi Chemical Corporation, Japan) dissolved at a polymer concentration of 41 mg / mL in a mixture of α-terpineol (purchased from Sigma-Aldrich, Singapore) and triethylene glycol (purchased from Sigma-Aldrich, Singapore) (7:1 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0197] Example 1c

[0198] 0.22 mL of 40% hydrolyzed polyvinyl alcohol dissolved in a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) at a polymer concentration of 41 mg / mL was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0199] Figure 1C This is an SEM of a cross-section of the main portion of a 120 μm thick metal composite of silver flakes (average size 5 to 8 μm) formulated with diethylene glycol dimethyl ether, glycerol and ethylene glycol (6.0:0.5:1.5 volume ratio) and pressurelessly sintered at 160°C in nitrogen for 30 minutes as described in Example 1c using 0.7 weight percent of 40% hydrolyzed polyvinyl alcohol.

[0200] Figure 1D yes Figure 1C SEM of the cross section at the interface between the metal composite and native SiO2 / Si shown in FIG.

[0201] Example 1d

[0202] 0.22 mL of 40% hydrolyzed polyvinyl alcohol dissolved at a polymer concentration of 41 mg / mL in a mixture of propylene glycol methyl ether acetate (purchased from Sigma-Aldrich, Singapore), diethylene glycol (purchased from Sigma-Aldrich, Singapore), and tetralin (purchased from Sigma-Aldrich, Singapore) (5:2:1 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 8 to 12 μm; tap density = 3.5 to 4.2 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.0m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0203] Figure 1E is an SEM of a cross-section of the bulk of a 110 μm thick metal composite of silver flakes (average size 8 to 12 μm) formulated with propylene glycol methyl ether acetate, diethylene glycol and tetralin (5:2:1 volume ratio) and pressurelessly sintered at 160°C in nitrogen for 30 minutes as described in Example 1d using 0.7 weight percent of 40% hydrolyzed polyvinyl alcohol.

[0204] Figure 1F yes Figure 1E SEM of the cross section at the interface between the metal composite and native SiO2 / Si shown in FIG.

[0205] Figures 1A to 1F It was shown that the metal composites tested contained dense and substantially fused aggregates of silver powder without microscopic voids or polymer phases (regardless of the size of the silver flakes) and without visible polymer "binder". Micrographs at the SiO2 / Si interface revealed conformal and tight packing of the silver flakes to the interface. In some cases, a sub-micron thick silver film appeared to have been deposited on the SiO2. This explains the unexpectedly good adhesion to the substrate.

[0206] Example 1e

[0207] 0.22 mL of poly(hydroxystyrene) dissolved at a polymer concentration of 54 mg / mL in a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 8 to 12 μm; tap density = 3.5 to 4.2 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.0m 2 / g) to obtain a paste containing 81.7 weight percent silver, 1.0 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 15 minutes.

[0208] Example 1f

[0209] 0.22 mL of poly(ethyleneimine) (purchased from Sigma-Aldrich, Singapore) dissolved at a polymer concentration of 27 mg / mL in a mixture of α-terpineol and triethylene glycol (7:1 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 8 to 10 μm; tap density = 2.8 to 3.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.7 to 1.3m 2 / g) to obtain a paste containing 82.1 weight percent silver, 0.5 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0210] Example 1g

[0211] 0.22 mL of 40% hydrolyzed polyvinyl alcohol dissolved in a mixture of α-terpineol and triethylene glycol (7:1 volume ratio) at a polymer concentration of 41 mg / mL was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 8 to 10 μm; tap density = 2.8 to 3.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.7 to 1.3m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0212] Example 1h

[0213] 0.22 mL of 40% hydrolyzed polyvinyl alcohol dissolved in a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) at a polymer concentration of 41 mg / mL was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 8 to 10 μm; tap density = 2.8 to 3.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.7 to 1.3m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0214] Example 1i

[0215] 0.22 mL of polyvinyl butyral (purchased from Sigma-Aldrich, Singapore) dissolved at a polymer concentration of 41 mg / mL in a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0216] Example 2 - Preparation of paste using silver spheres and modifier polymer

[0217] The following examples show pastes with silver spheres and a modifier polymer formulated by first dissolving the modifier polymer into a solvent system and then mixing with the metal powder.

[0218] Example 2a

[0219] 0.21 mL of polyethyleneimine dissolved in a mixture of α-terpineol and glycerol (7.5:0.5 volume ratio) at a polymer concentration of 68 mg / mL was mixed with 1.2 g of silver spheres (manufacturer specifications: diameter = 6 μm; tap density = 4.0 g / cm) on a vortex mixer and bath sonicator. 3 ) to obtain a paste containing 84.7 weight percent silver, 1.0 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 34 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0220] Example 2b

[0221] 0.11 mL of polyethyleneimine dissolved at a polymer concentration of 126 mg / mL in a mixture of α-terpineol and glycerol (7:1 volume ratio) was mixed with 1.2 g of silver spheres (manufacturer specifications: diameter = 6 μm; tap density = 4.0 g / cm) on a vortex mixer and bath sonicator. 3 ) to obtain a paste containing 90.7 weight percent silver, 1.1 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 47 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was partially sealed with a cover glass and then heated to 200°C in nitrogen at a single ramp rate of 3°C per minute and kept at this temperature for 30 minutes.

[0222] Example 3 - Preparation of paste using silver flakes coated with modifier polymer

[0223] The following examples illustrate the preparation of silver flakes coated with a modifier polymer and a paste formulated by mixing the silver flakes coated with a modifier polymer into a solvent system.

[0224] Example 3a

[0225] 1.2 mL of polyvinyl pyrrolidone (purchased from Sigma-Aldrich, Singapore) dissolved in ethylene glycol at a polymer concentration of 60 mg / mL was mixed with 3.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and let it stand overnight. Add 12mL of ethylene glycol and separate the silver flakes by centrifugation. The silver flakes were rinsed with water, separated by centrifugation, rinsed with 12 mL of isopropanol (purchased from Sigma-Aldrich, Singapore), separated by centrifugation, and finally dried in vacuo. 0.22 mL of a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) was mixed with 1.0 g of the polymer-coated silver flakes on a vortex mixer and a bath sonicator to obtain a paste containing 82.6 weight percent of silver and the remainder of solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent of silver. The preparation was applied to a native SiO2 / Si substrate using a spatula until the wet thickness was 250 μm and the area was 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0226] Example 3b

[0227] 1.2 mL of poly(2-hydroxyethyl methacrylate) dissolved in ethylene glycol at a polymer concentration of 60 mg / mL (purchased from Sigma-Aldrich, Singapore) was mixed with 3.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and let it stand overnight. Add 12mL of ethylene glycol and separate the silver flakes by centrifugation. The silver flakes were rinsed with water, separated by centrifugation, rinsed with 12 mL of isopropanol, separated by centrifugation, and finally dried in vacuo. 0.22 mL of a mixture of diethylene glycol dimethyl ether, glycerol, and ethylene glycol (6.0:0.5:1.5 volume ratio) was mixed with 1.0 g of the polymer-coated silver flakes on a vortex mixer and a bath sonicator to obtain a paste containing 82.6 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent silver. The preparation was applied to a native SiO2 / Si substrate using a spatula until the wet thickness was 250 μm and the area was 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0228] Example 3c

[0229] 1.2 mL of 80% hydrolyzed polyvinyl alcohol (available from Mitsubishi Chemical Corporation, Japan) dissolved in ethylene glycol at a polymer concentration of 60 mg / mL was mixed with 3.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and let it stand overnight. Add 12mL of ethylene glycol and separate the silver flakes by centrifugation. The silver flakes were rinsed with water, separated by centrifugation, rinsed with 12 mL of isopropanol, separated by centrifugation, and finally dried in vacuo. 0.22 mL of a mixture of propylene glycol methyl ether acetate (purchased from Sigma-Aldrich, Singapore), diethylene glycol, and tetralin (5:2:1 volume ratio) was mixed with 1.0 g of the polymer-coated silver flakes on a vortex mixer and a bath sonicator to obtain a paste containing 82.6 weight percent of silver and the remainder of solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent of silver. The preparation was applied to a natural SiO2 / Si substrate using a spatula until the wet thickness was 250 μm and the area was 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0230] Example 4 - Preparation of paste using silver flakes coated with modifier polymer in diethylene glycol dimethyl ether

[0231] The following examples are pastes formulated by mixing silver flakes coated with a modifier polymer into diethylene glycol dimethyl ether.

[0232] Example 4a

[0233] 0.22 mL of diethylene glycol dimethyl ether was mixed with 1.0 g of silver flakes coated with poly(2-hydroxyethyl methacrylate) (as described in Example 3b) on a vortex mixer and bath sonicator to obtain a paste containing 82.6 weight percent silver and the remainder solvent. This formulation corresponds to 30 volume percent silver based on the total volume of the formulation. The formulation was applied to a native SiO2 / Si substrate using a doctor blade to a wet thickness of 250 μm and an area of ​​8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, then injected with 0.02 mL of a mixture of geraniol and diethylene glycol in a volume ratio of 1:1, pasted on the glass coated with the fluoropolymer, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes.

[0234] Example 5 - Preparation of a paste without a modifier polymer

[0235] The following example is a paste formulated by mixing silver flakes into a solvent system. This example can be used as a thermal interface material or die attach material for metallized surfaces, such as direct bonded copper, or contacts, respectively.

[0236] Example 5a

[0237] 0.22 mL of a mixture of α-terpineol and triethylene glycol (7:1 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 82.6 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 100°C for 20 minutes in air, and the glass coated with the fluoropolymer was attached, and then heated to 200°C at a heating rate of 7.5°C per minute in nitrogen and kept at a constant temperature for 30 minutes.

[0238] Example 5b

[0239] A mixture of 0.33 mL of propylene glycol methyl ether acetate, geraniol (purchased from Sigma-Aldrich, Singapore), and diethylene glycol (2:4:4 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 75.4 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 23 volume percent silver. The preparation is dispensed onto a natural SiO2 / Si substrate. A glass coated with a fluorine-containing polymer is attached to the paste, and then heated from 60°C to 160°C in nitrogen at a heating rate of 3°C per minute, and kept at a constant temperature for 30 minutes.

[0240] Example 5c

[0241] 0.33 mL of a mixture of propylene glycol methyl ether acetate, α-terpineol, and diethylene glycol (2:4:4 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 75.4 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 23 volume percent silver. The preparation is dispensed onto a natural SiO2 / Si substrate. A glass coated with a fluorine-containing polymer is attached to the paste, and then heated from 60°C to 160°C in nitrogen at a heating rate of 3°C per minute, and kept at a constant temperature for 30 minutes.

[0242] Example 5d

[0243] 0.33 mL of a mixture of propylene glycol methyl ether acetate, α-terpineol, and diethylene glycol (2:4:4 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and 0.05g of silver oxide (purchased from Sigma-Aldrich in Singapore) were mixed to obtain a paste containing 71.8 weight percent of silver, 3.8 weight percent of silver oxide (purchased from Sigma-Aldrich in Singapore) and the remainder of solvent. Based on the total volume of the preparation, this preparation corresponds to 23 volume percent of silver. The preparation is dispensed onto a natural SiO2 / Si substrate. A glass coated with a fluorine-containing polymer is attached to the paste, and then heated from 60°C to 160°C in nitrogen at a heating rate of 3°C per minute, and kept at a constant temperature for 30 minutes.

[0244] Example 5e

[0245] 0.51 mL of a mixture of propylene glycol methyl ether acetate, α-terpineol, and diethylene glycol (2:4:4 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and 0.15g of silver oxide were mixed to obtain a paste containing 60.2 weight percent silver, 9.0 weight percent silver oxide and the remainder of solvent. Based on the total volume of the preparation, this preparation corresponds to 16 volume percent silver. The preparation is dispensed onto a natural SiO2 / Si substrate. A glass coated with a fluorine-containing polymer is attached to the paste, and then heated from 60°C to 160°C in nitrogen at a heating rate of 3°C per minute, and kept at a constant temperature for 30 minutes.

[0246] Example 5f

[0247] 0.28 mL of a mixture of propylene glycol methyl ether acetate, α-terpineol, and diethylene glycol (3:5:2 volume ratio) was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 76.5 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 26 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with the fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 3°C per minute and kept at a constant temperature for 30 minutes.

[0248] Summary of Examples

[0249] The exemplary formulations according to the present application as described above illustrate the wide variety of high performance pastes that can be achieved in order to cover a wide variety of applications. Without further optimization, the DC conductivity of films made from these formulations is already better than 1.0×10 5 S / cm, corresponding to a thermal conductivity better than 75 W / mK. In many cases, the DC conductivity of the membrane is better than 1.2×10 5 S / cm, corresponding to a thermal conductivity better than 90 W / mK. In some cases, the DC conductivity of the membrane is better than 1.4×10 5 S / cm, and the corresponding thermal conductivity is better than 105W / mK.

[0250] The lap shear strengths of untreated smooth natural SiO2 are generally better than 1 MPa. In some cases, they are better than 2 MPa.

[0251] In a typical experimental protocol, the silver paste was formulated as described above and coated onto a silicon wafer with native oxide by doctor blade until a wet thickness of 250 μm and a 8×8 mm 2 area. A general drying and sintering temperature-time curve was applied without optimization and without any pressure on the paste film. Typically, after pre-drying at 60°C in air for 20 minutes, a glass coated with a fluoropolymer is applied to simulate the attachment of a second component (but can be removed to measure conductivity), then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept constant for 15 minutes. In some experiments, heating to 200°C was performed at a single heating rate of 3°C per minute and kept constant for 30 minutes. The applied paste was partially closed with a cover glass to slow down solvent evaporation.

[0252] Flake and spherical silver powders were tested. Even for spherical silver powders, high conductivity was obtained in pressureless sintering at or below 200° C. in an inert atmosphere, demonstrating the effectiveness and practicality of the paste of the present invention. However, the sintered spherical silver film had no adhesion to native SiO2.

[0253] Heating is performed on a digital hot plate first calibrated with a melting point standard. DC conductivity is measured by a four-point probe method and corrected for film thickness and size. Microvolt voltage is measured using a high-precision microvoltmeter. Film thickness is measured using a profilometer or a micrometer. Thermal conductivity is estimated by the Wiedemann-Franz law, in which the ratio of thermal conductivity to electrical conductivity is considered a constant because free electrons provide heat and electrical transport in metals. Lap shear strength is measured in a homemade tool, which is attached to the bottom surface of the si tube core and the top surface of the sintered metal film using double-sided tape. Reliable measurements are limited to 2MPa due to adhesion failure of the fixing tape, but this is enough to prove that even for demanding substrates (e.g., natural SiO2), sufficient adhesion strength is also present. The preparation is well sintered onto silver, gold, platinum and palladium surfaces.

[0254] In summary, the conductivity of the above examples is better than 1.0×10 5 S / cm. According to the Wiedemann-Franz law, the corresponding thermal conductivity for the silver powder composite is estimated to be better than 75 W / mK. The adhesion strength of the above silver flake preparations to the native SiO2 / Si surface is generally higher than 1 MPa. In contrast, in the absence of the modifier polymer and the co-deoxidizer solvent, the adhesion strength is less than 0.1 MPa.

[0255] Comparative Example 1- Conductive silver paint

[0256] Conductive silver paint (Ted Pella Inc, product number 16062) was used as received and applied by doctor blade onto a native SiO2 / Si substrate to a wet thickness of 250 μm over an area of ​​8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, and the glass coated with fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. The conductivity of this comparative example is 2×10 4 S / cm.

[0257] Comparative Example 2 - Silver Flakes in Ethylene Glycol

[0258] Ethylene glycol is a common solvent in the art. 0.22 mL of ethylene glycol was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 82.6 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 90°C in air for 15 minutes, and the glass coated with fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. The conductivity of this comparative example is 2×10 4 S / cm. Comparative Example 3 - Silver flakes in α-terpineol

[0259] 0.22 mL of α-terpineol was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 82.6 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 100°C in air for 15 minutes, and the glass coated with fluoropolymer was attached, and then heated to 200°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. The conductivity of this comparative example is 8×10 4 S / cm.

[0260] Comparative Example 4 - Silver flakes and poly(hydroxystyrene) in α-terpineol

[0261] 0.22 mL of 40% hydrolyzed polyvinyl alcohol dissolved in α-terpineol was mixed with 1.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) to obtain a paste containing 81.9 weight percent silver, 0.7 weight percent polymer and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 29 volume percent silver. The preparation is applied to a natural SiO2 / Si substrate using a doctor blade until the wet thickness is 250 μm and the area is 8×8 mm 2 The paste was pre-dried at 100°C in air for 15 minutes, and the glass coated with fluoropolymer was attached, and then heated to 200°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. The conductivity of this comparative example is 8×10 4 S / cm.

[0262] Comparative Example 5 - Silver flakes and polyvinyl pyrrolidone in propylene glycol methyl ether acetate

[0263] 1.2 mL of polyvinyl pyrrolidone dissolved in ethylene glycol at a polymer concentration of 60 mg / mL was mixed with 3.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and let it stand overnight. Add 12mL of ethylene glycol and separate the silver flakes by centrifugation. The silver flakes were rinsed with water, separated by centrifugation, rinsed with 12 mL of isopropanol, separated by centrifugation, and finally dried in vacuo. 0.22 mL of propylene glycol methyl ether acetate was mixed with 1.0 g of the pre-exchanged silver flakes on a vortex mixer and a bath sonicator to obtain a paste containing 82.6 weight percent silver and the remainder solvent. Based on the total volume of the preparation, this preparation corresponds to 30 volume percent silver. The preparation was applied to a native SiO2 / Si substrate using a spatula until the wet thickness was 250 μm and the area was 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, the glass coated with fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. This comparative example was not sintered.

[0264] Comparative Example 6 - Silver flakes and poly(2-hydroxyethyl methacrylate) in diethylene glycol dimethyl ether

[0265] 1.2 mL of poly(2-hydroxyethyl methacrylate) dissolved in ethylene glycol at a polymer concentration of 60 mg / mL was mixed with 3.0 g of silver flakes (manufacturer specifications: flake size = 5 to 8 μm; tap density = 2.2 to 2.8 g / cm) on a vortex mixer and bath sonicator. 3 ; Specific surface area = 0.6 to 1.2m 2 / g) and let it stand overnight. Add 12mL of ethylene glycol and separate the silver flakes by centrifugation. The silver flakes were rinsed with water, separated by centrifugation, rinsed with 12 mL of isopropanol, separated by centrifugation, and finally dried in vacuo. 0.22 mL of diethylene glycol dimethyl ether was mixed with 1.0 g of the pre-exchanged silver flakes on a vortex mixer and a bath sonicator to obtain a paste containing 82.6 weight percent silver and the remainder solvent. This formulation corresponds to 30 volume percent silver based on the total volume of the formulation. The formulation was applied to a native SiO2 / Si substrate using a spatula until the wet thickness was 250 μm and the area was 8×8 mm 2 The paste was pre-dried at 60°C in air for 20 minutes, the glass coated with fluoropolymer was attached, and then heated to 160°C in nitrogen at a heating rate of 7.5°C per minute and kept at a constant temperature for 30 minutes. This comparative example was not sintered.

[0266] Industrial Applicability

[0267] The compositions and composites of the present disclosure can be used in a variety of applications, such as electrically and thermally conductive materials, thermal interfaces, die attach, electrical interconnects, and electrode materials.

[0268] It will be apparent to those skilled in the art after reading the foregoing disclosure that various other modifications and adaptations of the present invention will be apparent without departing from the spirit and scope of the invention, and all such modifications and adaptations are intended to fall within the scope of the appended claims.

Claims

1. A composition comprising a deoxidizer solvent, a cosolvent, and a plurality of silver particles suspended in a mixture of the deoxidizer solvent and the cosolvent, wherein the deoxidizer solvent comprises one or more compounds of formula C n O m H 2n+2-p (OH) p wherein n, m and p are integers, provided that 1≤(n+m) / p≤8, and The mixture of the deoxidizer solvent and the co-solvent contains hydroxyl groups at a concentration of 2M to 20M.

2. The composition according to claim 1, wherein The deoxidizer solvent and the co-solvent have a combined weight percentage of 6 weight percent to 30 weight percent based on the total weight of the composition.

3. The composition according to claim 1 or 2, wherein the plurality of silver particles are in the form of flakes, granules, spheres, or a combination thereof.

4. The composition according to any one of claims 1 to 3, wherein the plurality of silver particles comprises elemental silver particles, silver alloy particles, silver-coated particles, silver oxide particles, or a combination thereof.

5. The composition according to any one of claims 1 to 4, wherein the deoxidizer solvent has a boiling point of 190°C to 350°C.

6. The composition according to any one of claims 1 to 5, wherein the deoxidizer solvent is selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, isomers of propylene glycol, isomers of butanediol, isomers of pentanediol, isomers of hexanediol, isomers of heptanediol, isomers of octanediol, glycerol, pentaerythritol, dipentaerythritol, 2-(2-methoxyethoxy)ethanol, 2-(2-ethoxyethoxy)ethanol, and combinations thereof.

7. The composition of any one of claims 1 to 6, wherein the co-solvent has a boiling point of 60°C to 350°C.

8. The composition according to any one of claims 1 to 7, wherein the co-solvent comprises one or more polarizable groups selected from alkenyl, aryl, carbonyl or ether groups.

9. The composition according to any one of claims 1 to 8, wherein the co-solvent is selected from the group consisting of xylene isomers, mesitylene, tetralin, terpinene, limonene, linalool, α-terpineol, geraniol, citronellol, diethylene glycol dimethyl ether, 1,2-dibutoxyethane, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, diethylene glycol butyl ether, tripropylene glycol methyl ether, triethylene glycol ethyl ether, triethylene glycol butyl methyl ether, triethylene glycol butyl ether, propylene glycol methyl ether, cyclopentane Butyl sulfone, 2-(2-butoxyethoxy)ethanol, phenoxyethanol, 2-(benzyloxy)ethanol, di(propylene glycol) methyl ether, 2-butoxyethanol acetate, ethylene glycol diacetate, propylene glycol methyl ether acetate, di(propylene glycol) methyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, ethylene glycol monobutyl ether acetate, 2-ethoxyethyl acetate, ethylene glycol monoethyl ether acetate, 2-butoxyethyl acetate, ethanolamine, diethanolamine, Texanol TM The invention relates to a group consisting of ester alcohol, diethyl adipate, dimethyl succinate, methyl benzoate, N-methylpyrrolidone, γ-butyrolactone, diethyl carbonate, propylene carbonate, safrole, anethole, cyclohexanone, cyclohexanol, carvone, ethyl sorbate, pseudoionone, farnesene, 2,6-dimethyl-2,4,6-octatriene, o-cresol, methyl salicylate and combinations thereof.

10. The composition of any one of claims 1 to 9, further comprising a modifier polymer.

11. The composition according to any one of claims 1 to 10, further comprising a reducing metal.

12. A method of forming a composition comprising the steps of dispersing a plurality of silver particles in a deoxidizer solvent in the presence of a cosolvent or dispersing a plurality of silver particles in a mixture of a deoxidizer solvent and a cosolvent.

13. A method of forming a composite material comprising the step of sintering a composition according to any one of claims 1 to 11 on a substrate.

14. The method of claim 13, wherein the sintering step is performed at a temperature of 140°C to 200°C.

15. A method according to claim 13 or 14, wherein the sintering step is carried out in an inert atmosphere.

16. A method according to any one of claims 13 to 15, further comprising the step of pre-drying the composition prior to the sintering step.

17. A method according to any one of claims 13 to 16, further comprising the step of contacting the composition with a second substrate or component prior to the sintering step.

18. The method of claim 17, wherein the one or more substrates are selected from the group consisting of electronic components and thermal components.

19. A device comprising a composite material formed by the method of any one of claims 13 to 18.